Experimental fossilization of mat‐forming cyanobacteria in coarse‐grained siliciclastic sediments. Issue 4 (11th February 2017) - Newman, S. A.; Klepac‐Ceraj, V.; Mariotti, G.; Pruss, S. B.; Watson, N.; Bosak, T.
Abstract: Microbial fossils and textures are commonly preserved in Ediacaran and early Cambrian coarse‐grained siliciclastic sediments that were deposited in tidal and intertidal marine settings. In contrast, the fossilization of micro‐organisms in similar marine environments of post‐Cambrian age is less frequently reported. Thus, temporal discrepancies in microbial preservation may have resulted from the opening and closing of a unique taphonomic window during the terminal Proterozoic and early Phanerozoic, respectively. Here, we expand upon previous work to identify environmental factors which may have facilitated the preservation of cyanobacteria growing on siliciclastic sand, by experimentally determining the ability of microbial mats to trap small, suspended mineral grains, and precipitate minerals from ions in solution. We show that (i) fine grains coat the sheaths of filamentous cyanobacteria (e.g., Nodosilinea sp.) residing within the mat, after less than 1 week of cell growth under aerobic conditions, (ii) clay minerals do not coat sterile cellulose fibers and rarely coat unsheathed cyanobacterial cells (e.g., Nostoc sp.), (iii) stronger disturbances (where culture jars were agitated at 170 rpm; 3 mm orbital diameter) produce the smoothest and most extensive mineral veneers around cells, compared with those agitated at slower rotational speeds (150 and 0 rpm), and (iv) mineral veneers coating cyanobacterial cells are ~1 μm in width. These new findings suggest that sheathed filamentous cyanobacteria may be preferentially preserved under conditions of high fluid energy. We integrate these results into a mechanistic model that explains the preservation of microbial fossils and textures in Ediacaran sandstones and siltstones, and in fine‐grained siliciclastic deposits that contain exceptionally preserved microbial mats.